2012
DOI: 10.1002/jctb.3803
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous removal of TOC and TSS in swine wastewater using the partial nitritation process

Abstract: BACKGROUND: Considering biological nitrogen removal, the partial nitritation connected with the anaerobic ammonium oxidation (anammox) process is a promising alternative for nitrogen elimination at high loading rates. The objective of the present study was to evaluate the establishment and operation of a partial nitritation process in an airlift reactor with simultaneous removal of total organic carbon and suspended solids using swine wastewater.RESULTS: The partial nitritation reactor was inoculated with a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 27 publications
0
4
0
5
Order By: Relevance
“…Interestingly, the observed acclimation period was much shorter than the 100 to 175 days (Jubany et al, 2008) reported for other nitrification systems treating swine wastewater. The rapid acclimation time obtained in this study was most likely due to the use of a diluted raw effluent (1:10 v/v), which minimizes the inhibitory effects of high influent NH3 concentrations on microorganisms (De Prá et al, 2012). Therefore, the use of a diluted wastewater influent during the initial MLE start up process could minimize time required to establish steady-state conditions at field-scale operations.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, the observed acclimation period was much shorter than the 100 to 175 days (Jubany et al, 2008) reported for other nitrification systems treating swine wastewater. The rapid acclimation time obtained in this study was most likely due to the use of a diluted raw effluent (1:10 v/v), which minimizes the inhibitory effects of high influent NH3 concentrations on microorganisms (De Prá et al, 2012). Therefore, the use of a diluted wastewater influent during the initial MLE start up process could minimize time required to establish steady-state conditions at field-scale operations.…”
Section: Resultsmentioning
confidence: 93%
“…A fermentação de materiais ricos em ureia e proteínas libera amônia. Em função do pH e temperatura do meio reacional, pode-se ter uma geração elevada de amônia livre (De Prá et al 2013). O equilíbrio químico do sistema para formação de amônia livre (AL) pode ser calculado através da Equação 2.…”
Section: Nitrogênio Amoniacal E Amônia Livreunclassified
“…Dentre as alternativas para favorecer o acúmulo de nitrito nos sistemas biológicos, as principais se baseiam na regulação apropriada de parâmetros de controle como oxigênio dissolvido (OD), tempo de aeração, temperatura, tempo de retenção hidráulica (TRH), tempo de retenção de sólidos (TRS), pH, amônia livre (AL), ácido nitroso livre (ANL) e inibidores químicos (Cui, 2012;De Prá, 2013). Contudo, é necessário avaliar, além das vantagens e limitações, a viabilidade econômica do processo quando da utilização destas estratégias.…”
Section: Processo De Nitritação Parcialunclassified